Reciprocity and payment schemes: when equality is unfair - Johannes Abeler; Steffen Altmann; Sebastian Kube; Matthias Wibral (Institute for the Study of Labor (IZA), 2006)
A growing literature stresses the importance of reciprocity, especially for employment relations. In this paper, we study the interaction of different payment modes with reciprocity. In particular, we analyze how equal wages affect performance and efficiency in an environment characterized by contractual incompleteness. In our experiment, one principal is matched with two agents. The principal pays equal wages in one treatment and can set individual wages in the other. We find that the use of equal wages elicits substantially lower efforts and efficiency. This is not caused by monetary incentives per se since under both wage schemes it is profit-maximizing for agents to exert high efforts. The treatment difference is rather driven by the fact that reciprocity is violated far more frequently in the equal wage treatment. Agents suffering from a violation of reciprocity subsequently withdraw effort. Our results suggest that individual reward and punishment opportunities are crucial for making reciprocity a powerful contract enforcement device.
urn:nbn:de:101:1-20080509145
Keywords: 330